The Intersection of Science and Technology in Promoting Child Safety and Protection - Mustafa Hassan Zain; Salman Hakim; Karim Rahim Faisal (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The safety and protection of children in the digital age require innovative approaches involving both science and technology. This paper examines how technological advancements, such as online monitoring systems, AI-driven safety tools, and data protection measures, are helping to safeguard children from online threats and harm. The study discusses current trends and the potential for further innovation in child safety, focusing on both the risks and benefits of these technologies in creating safer environments for children.